ETHICAL CLOTHING IN HADITH AND ITS RELEVANCE TO THE DRESS STYLE OF TODAY'S YOUTH - Fitri, Nova Anggriana; Muttaqin, Khairul (UNIVERSUM: Jurnal Keislaman dan Kebudayaan, 2025)
This study discusses the concept of clothing ethics in the Hadith and its relevance to the dressing style of contemporary Muslim youth. In Islam, clothing is not merely a physical or cultural necessity but also a moral and spiritual obligation that reflects faith, modesty, and personal dignity. This research employs a library research method with a thematic-conceptual approach to the Hadith, drawing on primary sources from Kutub al-Tis’ah and secondary references such as classical commentaries, scholarly books, and academic journals. The findings reveal that the Prophet’s traditions emphasize several key principles of dress: covering the body appropriately, avoiding arrogance and extravagance in clothing, refraining from imitating the opposite gender, and maintaining simplicity and sincerity of intention. These values remain highly relevant in the modern context, where fashion trends often create a dilemma between religious commitment and popular cultural influences. Therefore, Islamic educational institutions are encouraged to develop a more humanistic and educational approach to da’wah to guide young generations to balance self-expression with moral responsibility. The Hadith-based ethics of clothing can serve as a timeless guide for Muslim youth to express a modern identity while remaining virtuous and dignified.